1991
DOI: 10.1037/1040-3590.3.2.202
|View full text |Cite
|
Sign up to set email alerts
|

Disruptive behaviors in an outpatient pediatric population: Additional standardization data on the Eyberg Child Behavior Inventory.

Abstract: This study presents information on disruptive behaviors in an outpatient pediatric population. The Eyberg Child Behavior Inventory (ECBI), a parent rating scale of disruptive behaviors, was completed on 1,526 children at 5 pediatric clinics in 4 Northwestern states (Idaho, Montana, Oregon, and Washington). The results indicated that 10.40% of the children not in treatment for learning or behavioral problems scored in the clinical range on the ECBI. Children in the 2-5 years age range with a family income of le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 9 publications
2
31
1
Order By: Relevance
“…15,16 However, in contrast with previous research 18 that suggests that girls with PNE have more behavioral comorbidity than boys with PNE, results from the current study suggest boys with PNE have more behavior problems than girls with PNE. The percentage of girls with PNE who scored in the clinically significant range on the ECBI was approximately equal to that in the nonclinical sample (17% and 13%, respectively), and was much lower than that in the clinical sample (60%).…”
Section: Commentcontrasting
confidence: 55%
“…15,16 However, in contrast with previous research 18 that suggests that girls with PNE have more behavioral comorbidity than boys with PNE, results from the current study suggest boys with PNE have more behavior problems than girls with PNE. The percentage of girls with PNE who scored in the clinically significant range on the ECBI was approximately equal to that in the nonclinical sample (17% and 13%, respectively), and was much lower than that in the clinical sample (60%).…”
Section: Commentcontrasting
confidence: 55%
“…Intensity and Problem subscales on the 36-item ECBI (Eyberg & Pincus, 1999) served as the dependent measure of behavior change due to the availability of normative data sensitive to age (2 to 16 years old; Burns & Patterson, 1991; Burns, Patterson, Nussbaum, & Parker, 1991) and established psychometrics with low-income samples (e.g., Fernandez et al, 2011). For each item, caregivers rate the intensity of the behavior (0 = never to 7 = always ) and whether each behavior is a problem (0 = no; 1 = yes).…”
Section: Methodsmentioning
confidence: 99%
“…The ECBI has been well validated in both clinic-referred and non-referred samples and has demonstrated good reliability and validity. 15,[35][36][37][38][39][40] The original ECBI was not validated in African American samples; however, the newer version published in 1999 does not differ substantially from the older version used in this study and is reported to have an internal consistency of .97 for the African American subgroup in the standardization sample. 41 …”
Section: Methodsmentioning
confidence: 99%